The Effect Of Hard Protein Corona On Qd Nanoparticle Towards Senescent Cells - Foroozandehasl, Seyedeh Parisa (2019)
Nanomedicine is an important area of study that examines the utilization of nanomaterials and nanoparticles in medical therapy and diagnostic purposes. However, not many studies have focused on the aging related aspect of nanomedical research that could have been valuable in treating aging associated diseases such as Werner syndrome, sarcopenia and Alzheimer’s. In the present work, the cytotoxic potential of PEGylated quantum dots (QD-PEG) and hard protein corona coated QD-PEG (QD-HC) on cells of opposing age groups were examined. In the initial phase of the study, the interaction of QDs with proteins from human blood plasma were analyzed. The results have shown that protein corona was able to form on pristine QD-PEG based on SDS-PAGE, MALDITOF/ TOF, LC-MS/MS and μBCA analysis. Formation of hard protein corona had transformed its physicochemical properties, which had in turn affected the colloidal stability of QD-PEG in a significant manner. At proportionate levels of nanoparticle concentration, hard protein corona had imbued distinct photonic and colloidal characteristics to QD-PEG that were better suited for nanomedical applications in terms of: (1) enhanced photostability at extreme pH conditions, (2) greater resistance to changes in extracellular medium that induces agglomeration and gravitational sedimentation, and (3) increased robustness to degradation and leaching of QDs’ core materials at extreme pH conditions.